Attention Deficit Hyper Activity Disorder (ADHD) and Stress: A Mutual Relationship between Children and Mothers - Mercedeh Samiei; Reza Daneshmand; Rasul Keramatfar; Katayoon Khooshabi; Nasrin Amiri; Yadollah Farhadi; Seyedeh Zeinab Farzadfard; Hamid Kachooi; Roya Samadi (Basic and Clinical Neuroscience, 2015)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by high levels of inattention, hyperactivity and impulsivity which may result in mothers’ stress. The current study aims to compare stress among 45 mothers of ADHD children who had referred to “Rofeydeh psychiatric center” with 45 mothers of normal children. Methods: Brief demographic researcher-made questionnaire, Child Symptom Inventory-4 (CSI- 4), the Child Behavior Checklist (CBCL), and Parental Stress Index-Short Form (PSI/SF) were completed for each mother and child. Results: The results showed that except the component of acceptance, ADHD children had more problems in the field of attention compared with normal children. Mothers of ADHD children had also more stress compared with mothers of normal children. Discussion: ADHD can impair mothers’ mental health by inducing stress and this issue has important clinical and treatment implications. Specific treatment programs should be designed and implemented in Iran for the mothers of ADHD children to reduce stress among them and therefore, improve their mental health status.